How to design built environments around parks that ensure pedestrian safety. (September 2022) - Yu, Chia-Yuan; Woo, Ayoung
Abstract: Introduction: Safe and walkable routes to parks are associated with improved public health and increased park visits. Most studies on this topic have explored income and racial disparities in park access and safe routes to parks, and have not examined the influence of built environments on pedestrian safety around parks. To address this gap, this study explores the impacts of built environments on different scales (both street and neighborhood levels) on pedestrian safety around parks and determines whether this relationship varies by area income level. Method: Two-level negative binomial models were used to explore the relationship between the built environment and pedestrian crashes around parks and determine how the associations varied by high- and low-income areas in Orlando, FL. Resultsin both high: and low-income areas, increased commercial parcels and transit stops along street segments near parks were related to a higher number of pedestrian crashes, while single- and multi-family residential uses along street segments were related to fewer pedestrian crashes. Sidewalk coverage had a negative association with pedestrian-vehicle crashes, but only in low-income areas. Conclusions: The findings demonstrate that planners should consider and examine potential traffic conflict spots near commercial uses and transit stops. Moreover, residential areas are an appropriate land use type for future park site locations, ensuring park-related pedestrian safety. Furthermore, governments should improve sidewalk coverage to reduce pedestrian-vehicle crashes in low-income areas. Highlight: To explore the impacts of built environments on pedestrian-vehicle crashes around parks. More commercial parcels along street segments were related to more crashes. More transit stops along street segments were related to more pedestrian crashes. Sidewalk coverage were related to fewer crashes only in low-income areas. To inform planners to identify conflict spots near commercial uses and transit stops.